2018
DOI: 10.3390/ijms19030901
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Multiple Sclerosis 2017

Abstract: Multiple sclerosis (MS) is one of the most emerging fields in neurology. Recent pathophysiological insights have cleared the way for novel therapeutic strategies to combat disease aggravation. For instance, the B-cell depleting antibody ocrelizumab was recently approved for the treatment of relapsing-remitting (RRMS) and early primary progressive MS (PPMS). However, despite this progress, unmet medical necessities remain, especially for pediatric MS. Both new and more sophisticated therapeutic strategies and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Nie są jednak wymogiem diagnostycznym [14]. Jeśli pacjenci z CIS prezentowali unikalne prążki oligoklonalne w płynie mózgowo-rdzeniowym (CSF), konwersja do SM była ponad dwukrotnie bardziej prawdopodobna [17].…”
Section: Etiopatogenezaunclassified
“…Nie są jednak wymogiem diagnostycznym [14]. Jeśli pacjenci z CIS prezentowali unikalne prążki oligoklonalne w płynie mózgowo-rdzeniowym (CSF), konwersja do SM była ponad dwukrotnie bardziej prawdopodobna [17].…”
Section: Etiopatogenezaunclassified
“…As well, it was reported that MS incidence is linked to longitude, suggesting that ON incidence could vary between eastern and western parts of the world [2]. MS and ON are not considered to be hereditary diseases but genetic variations have been associated with greater risk and infectious agents have been considered as triggers [8,9].…”
Section: Introductionmentioning
confidence: 99%